Concealed Cyclotrimeric Polymorph of Lithium 2, 2, 6, 6‐Tetramethylpiperidide Unconcealed: X‐Ray Crystallographic and NMR Spectroscopic Studies. Issue 42 (9th September 2013) - Hevia, Eva; Kennedy, Alan R.; Mulvey, Robert E.; Ramsay, Donna L.; Robertson, Stuart D.
Abstract Lithium 2, 2, 6, 6‐tetramethylpiperidide (LiTMP), one of the most important polar organometallic reagents both in its own right and as a key component of ate compositions, has long been known for its classic cyclotetrameric (LiTMP)4 solid‐state structure. Made by a new approach through transmetalation of Zn(TMP)2 with tBuLi in n‐hexane solution, a crystalline polymorph of LiTMP has been uncovered. X‐ray crystallographic studies at 123(2) K revealed this polymorph crystallises in the hexagonal space group P63/m and exhibited a discrete cyclotrimeric (C3h) structure with a strictly planar (LiN)3 ring containing three symmetrically equivalent TMP chair‐shaped ligands. The molecular structure of (LiTMP)4 was redetermined at 123(2) K, because its original crystallographic characterisation was done at ambient temperature. This improved redetermination confirmed a monoclinic C2/c space group with the planar (LiN)4 ring possessing pseudo (non‐crystallographic) C4h symmetry. Investigation of both metalation and transmetalation routes to LiTMP under different conditions established that polymorph formation did not depend on the route employed but rather the temperature of crystallisation. Low‐temperature (freezer at −35 °C) cooling of the reaction solution favoured (LiTMP)3; whereas high‐temperature (bench) storage favoured (LiTMP)4. Routine 1H and 13C NMR spectroscopic studies in a variety of solvents showed that (LiTMP)3 and (LiTMP)4 exist in equilibrium, whereas 1H DOSY NMR studies gave diffusion coefficient results consistent with their relative sizes.